Influence of educational level on myocardial hypertrophy of hemodialysis patients - Martin, Rosana dos Santos e Silva [UNESP]; Franco, Roberto Jorge da Silva [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Zanati, Silméia Garcia [UNESP]; Barretti, Pasqual [UNESP]; Martin, Luis Cuadrado [UNESP]; Balbi, André Luis [UNESP]; Antunes, Aline Araújo [UNESP]; Martins, Antonio Sérgio [UNESP] (Sociedade Brasileira de Nefrologia, 2010)
Introduction: Chronic renal disease is associated with a high cardiovascular risk. Data from the general population associate cardiovascular diseases with low educational level, but no study has evaluated this association in patients on hemodialysis. Objective: This study aimed at evaluating the association between educational level, hypertension, and left ventricular hypertrophy in patients on chronic hemodialysis. Methods: A standard socioeconomic questionnaire was applied to 79 hemodialysis patients at the Hospital das Clínicas of Faculdade de Medicina de Botucatu, state of São Paulo. Clinical, laboratory and echocardiographic data were obtained from medical records. The patients were divided into two groups according to the median educational level, as follows: G1, patients with three or less years of schooling; G2, patients with more than three years of schooling. Results: Blood pressure, interdialytic weight gain, and variables statistically different in the two groups (p < 0.2) underwent multiple analysis. Independent associations were stated with p < 0.05 in multiple analysis. The mean age of patients was 57 ± 12.8 years, 46 were males (57%), and 53 white (67%). The variables selected for multiple analysis were: age (p = 0.004); educational level (p < 0.0001); body mass index (p = 0.124); left ventricular diameter (p = 0.048); and left ventricular mass index (p = 0.006). Antihypertensive drugs were similar in both groups. Systolic blood pressure (p = 0.006) and years of schooling (p = 0.047) had a significant and independent correlation with left ventricular mass index. Conclusion: In hemodialysis patients, left ventricular mass associated not only with blood pressure but also with educational level.

Introdução: A doença renal crônica apresenta elevado risco cardiovascular. Dados da popula- ção geral associam as doenças cardiovasculares a baixo nível de escolaridade, porém nenhum trabalho avaliou essa associação entre pacientes em hemodiálise. Objetivo: Avaliar a associação entre nível educacional, hipertensão e hipertrofia do ventrículo esquerdo em pacientes submetidos a hemodiálise crônica. Métodos: Foi aplicado um questionário socioeconômico padrão a 79 pacientes em hemodiálise, no Hospital das Clínicas da Faculdade de Medicina de Botucatu (UNESP). Dados clínicos, laboratoriais e ecocardiográficos foram extraídos dos prontuários. Os pacientes foram divididos em dois grupos de acordo com a mediana da escolaridade: o grupo I foi constituído por pacientes com escolaridade ≤ três anos, e grupo II por pacientes com escolaridade superior a três anos. Resultados: Pressão arterial, ganho de peso interdialítico e variáveis com diferença estatística entre os dois grupos ao nível de p < 0,2 foram selecionadas para análise múltipla. Na análise múltipla, associa- ções independentes foram consideradas ao ní- vel de p < 0,05. A média de idade dos pacientes foi 57 ± 12.8 anos, 46 pacientes eram homens (57%) e 53 eram brancos (67%). As variáveis selecionadas para análise múltipla foram: idade (p = 0,004), anos de escolaridade (p < 0,0001), índice de massa corpórea (p = 0,124), diâmetro do ventrículo esquerdo (p = 0,048) e índice de massa ventricular (p = 0,006). As drogas antihipertensivas empregadas foram similares em ambos os grupos. A pressão sistólica (p = 0,006) e a escolaridade (p = 0,047) apresentaram correlação significativa e independente com índice de massa ventricular. Conclusão: Em pacientes em hemodiálise, houve correlação da massa do ventrículo esquerdo não apenas com a pressão arterial, mas também com o nível educacional.
Influência da escolaridade na hipertrofia miocárdica de pacientes em hemodiálise
Keywords: Educational level; Left ventricular hypertrophy; Uremia; Dialysis; Hypertension; Escolaridade; Hipertrofia ventricular esquerda; Uremia; Hipertensão; Diálise